Dampak Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi di Indonesia - Awaliyah Matondang, Khairani; Sinurat, Penus; Zulfa ‘Afifah; Manurung, Tasya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this study is to analyze the consequences government spend on the financial stability of Indonesia and ascertain the extent to which spending by government affects economic growth. The data employed in this study is acquired from the Central Statistics Agency. This study utilizes a quantitative methodology that incorporates observable variables that may be measured. This study centers on the commercial commerce occurring in Indonesia. The tests utilized in this study encompass numerous linear regression evaluations, f tests, and variable of dependence tests. The research findings suggest that the corresponding coefficient of determination test produces a result of 54.7%, indicating that government spending explains 54.7% of the variability in economic growth. The regression test results in a Sig value of 0.048 for the federal government's expenditure variable, which indicates statistical significance at a significance level of 0.05. The calculated t value is 2.063. These data indicate that the state expenditure variable has a significant influence on the growing economy of Indonesia.